Transplantation of Wnt5a-modified Bone Marrow Mesenchymal Stem Cells Promotes Recovery After Spinal Cord Injury via the PI3K/AKT Pathway - Haimei Yang; Chaolun Liang; Junhua Luo; Xiuzhen Liu; Wanshun Wang; Kunrui Zheng; Dan Luo; Yu Hou; Da Guo; Dingkun Lin; Xiasheng Zheng; Xing Li (Molecular Neurobiology, 2024)
Spinal cord injury (SCI) is a severe neurological condition that can lead to paralysis or even death. This study explored the potential benefits of bone marrow mesenchymal stem cell (BMSC) transplantation for repairing SCI. BMSCs also differentiate into astrocytes within damaged spinal cord tissues hindering the cell transplantation efficacy, therefore it is crucial to enhance their neuronal differentiation rate to facilitate spinal cord repair. Wnt5a, an upstream protein in the non-classical Wnt signaling pathway, has been implicated in stem cell migration, differentiation, and neurite formation but its role in the neuronal differentiation of BMSCs remains unclear. Thus, this study investigated the role and underlying mechanisms of Wnt5a in promoting neuronal differentiation of BMSCs both in vivo and in vitro. Wnt5a enhanced neuronal differentiation of BMSCs in vitro while reducing astrocyte differentiation. Additionally, high-throughput RNA sequencing revealed a correlation between Wnt5a and phosphoinositide 3-kinase (PI3K)/protein kinase B(AKT) signaling, which was confirmed by the use of the PI3K inhibitor LY294002 to reverse the effects of Wnt5a on BMSC neuronal differentiation. Furthermore, transplantation of Wnt5a-modified BMSCs into SCI rats effectively improved the histomorphology (Hematoxylin and eosin [H&E], Nissl and Luxol Fast Blue [LFB] staining), motor function scores (Footprint test and Basso-Beattie-Bresnahan [BBB]scores)and promoted neuron production, axonal formation, and remodeling of myelin sheaths (microtubule associated protein-2 [MAP-2], growth-associated protein 43 [GAP43], myelin basic protein [MBP]), while reducing astrocyte production (glial fibrillary acidic protein [GFAP]). Therefore, targeting the Wnt5a/PI3K/AKT pathway could enhance BMSC transplantation for SCI treatment.